African Healing Shrines, Contextualized therapies and Specializations - Chiroma, Nathan H. (Regnum Publishers, 2021)
Throughout history, the quest for healing and wholeness outside conventional medicine has been a practice embraced by many. Medical pilgrimages outside of conventional hospitals were common practice in various eras in history. People travelled far and wide in the quest for healing in what is described as holy places such as shrines, prayer houses, monasteries and other locations. In Africa, the practice is not only gaining attention, but it is gaining more popularity, as a momentous social, spiritual and psychological issue. The existence of healing shrines and prayer houses are increasingly becoming popular, and many emerging themes and trends are adding new dimensions to the quest for healing and wholeness. One of the major emerging phenomena is that of specialisation. It is argued that specialisations are rooted either in heritage or calling as in the case of prayer houses. Specialisations are proving to be an important element in the healing sites. Specialisation in this context refers to the concentration on the healing of one or two ailments in a particular healing site. The focus of this chapter is to consider the dynamics of specialisation, especially as it occurs in healing shrines and prayer houses. Whereas healing shrines and prayer houses have been extensively studied in Africa, the aspect of specialisation has not received much attention among scholars. Specialisation as used in this chapter focuses only on one or two illnesses in a given healing shrine or prayer house.
Book Chapter
Keywords: African healing shrines; Christian Prayer Houses; Conventional medicine and healing; Specialised healers; Contextualised therapies